2015
DOI: 10.1177/1077801215590670
|View full text |Cite
|
Sign up to set email alerts
|

Making Meaning Out of Interpersonal Victimization

Abstract: Research examining meaning-making in the aftermath of interpersonal victimization among women has been restricted by quantitative methods and a focus on single distressing event. Qualitative methods were used to inspect meaning-making cognitions among a community sample of IPV (intimate partner violence) survivors. Consensus coding resulted in eight categories of meaning-making. The most widely endorsed cognition was self-blaming. Other strategies included justification for the abuser, normalizing violence, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
1
36
2
Order By: Relevance
“…Our findings additionally revealed that the day‐to‐day interaction with one's environment and one's community is particularly influential as one navigates daily healing after SV, particularly due to the mistrust survivors often feel after their experiences (Lonsway, ; Ranjbar & Speer, ). The impact of personal violation on one's worldview has been described by numerous qualitative studies, and can impact survivor autonomy as well as shatter their belief in a safe, benevolent world (Lilly, Valdez, & Graham‐Bermann, ; Lim, Adams, & Lilly, ; Lim, Valdez, & Lilly, ). Our findings indicate that environments or individuals that reinforce feelings of calm or goodness can be particularly powerful for challenging one's negative beliefs while promoting healing moments such as hope, freedom, and peace.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings additionally revealed that the day‐to‐day interaction with one's environment and one's community is particularly influential as one navigates daily healing after SV, particularly due to the mistrust survivors often feel after their experiences (Lonsway, ; Ranjbar & Speer, ). The impact of personal violation on one's worldview has been described by numerous qualitative studies, and can impact survivor autonomy as well as shatter their belief in a safe, benevolent world (Lilly, Valdez, & Graham‐Bermann, ; Lim, Adams, & Lilly, ; Lim, Valdez, & Lilly, ). Our findings indicate that environments or individuals that reinforce feelings of calm or goodness can be particularly powerful for challenging one's negative beliefs while promoting healing moments such as hope, freedom, and peace.…”
Section: Discussionmentioning
confidence: 99%
“…Online communities can provide a constructive forum for advice, support, and social contact in those who experience IPV (Hurley et al 2007;Lindgren 2014;Newberry 2017). IPV victimisation is often related to shame, self-blame, and social stigma (Eckstein 2016;Lim et al 2015), which may make it harder in terms of seeking support face-toface (Overstreet and Quinn 2013). The online environment facilitates interacting and sharing stories with others using an anonymous username, reducing stigma relating to disclosure and providing a degree of safeguarding.…”
mentioning
confidence: 99%
“…As Lim et al (2015) noted, “despite burgeoning prevention and intervention efforts, violence against women remains a widespread epidemic” (p. 1065). This is no truer than in female-headed families facing housing instability and homelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of social behavior are considered normative when individuals believe those behaviors are accepted by or prescriptive to themselves and others (Normative, 2017). Examined primarily within the context of corporal punishment and physical discipline (MacKenzie, Nicklas, Waldfogel, & Brookes-Gun, 2012; Patton, 2017; Taylor, Hamvas, & Paris, 2011) and in studies of interpersonal victimization (Lim, Valdez, & Lilly, 2015; Lindhorst & Tajima, 2008; McHugh, Livingston, & Ford, 2005), normativeness is highly influenced by one’s cultural, racial, and ethnic background; how individuals internalize and externalize family climate, parenting, and personal conflict; and how they then construct meaning from these experiences (Lansford et al, 2015; Vendlinski, Silk, Shaw, & Lane, 2006). Normativeness is thereby a belief system that is established in context to one’s environment over time and that categorizes certain actions and behaviors as “normal” within that context (Raghaven et al, 2006).…”
Section: Trauma Normativeness and Help Seekingmentioning
confidence: 99%